Biofilms in diabetic foot ulcers: impact, risk factors and control strategies - Afonso, Ana C. (2021)
Diabetic foot ulcers (DFUs) are a serious complication from diabetes mellitus, with a huge economic, social and psychological impact on the patients life. One of the main reasons why DFUs are so difficult to heal is related to the presence of biofilms. Biofilms promote wound inflammation and a remarkable lack of response to host defences/treatment options, which can lead to disease progression and chronicity. In fact, appropriate treatment for the elimination of these microbial communities can prevent the disease evolution and, in some cases, even avoid more serious outcomes, such as amputation or death. However, the detection of biofilm-associated DFUs is difficult due to the lack of methods for diagnostics in clinical settings. In this review, the current knowledge on the involvement of biofilms in DFUs is discussed, as well as how the surrounding environment influences biofilm formation and regulation, along with its clinical implications. A special focus is also given to biofilm-associated DFU diagnosis and therapeutic strategies. An overview on promising alternative therapeutics is provided and an algorithm considering biofilm detection and treatment is proposed.